Variability in energy cost of running at the end of a triathlon and a marathon - Hausswirth, C.; Bigard, A. X.; Berthelot, M.; Thomaidis, M.; Guezennec, C. Y. (International Journal of Sports Medicine, 1996)
The aim of this study was to investigate the increase in energy cost of running occurring at the end of a triathlon and a marathon event and to link them to the metabolic and hormonal changes, as well as to variations in stride length. Seven subjects took part in 3 experimental situations: a 2 h 15 min triathlon (30 min swimming, 60 min cycling and 45 min running), a 2 h 15 min marathon (MR) were the last 45 min were run at the same speed as the triathlon run (TR), and a 45 min isolated run (IR) done at triathlon speed. The results show that energy cost during MR was higher than during TR (p < 0.01) (+ 8.9%). Similar observations were made for pulmonary ventilation (+ 7.9%) and heart rate (+ 6.3%). Moreover, the values were significantly greater than the values obtained during the IR. TR and MR lead to greater weight loss (p < 0.01) (2.4 +/- 0.3 kg) than IR (1 +/- 0.2 kg). The triathlon and the marathon produced a large decrease in plasma volume (respectively 19.6 +/- 1.4% and 12.9 +/- 1.1%) compared to IR (2 +/- 0.4%). Plasma renin activity was higher for the triathlon and the marathon than for the IR (p < 0.01). MR produces a significantly greater increase in plasma free fatty acids (F.F.A.) than TR (p < 0.05) and IR (p < 0.01). In addition, the F.F.A. at the end of TR were significantly higher than IR (p < 0.05). At the end of the trial the mean stride lengths for TR and IR were greater (+ 15%) (p < 0.01) than for MR. This study, carried out with subjects running overground, confirms the decrease in running efficiency previously shown at the end of a laboratory triathlon, and demonstrates that this decrease is lower than that occurring during a marathon.